2019
DOI: 10.3390/jmse7090295
|View full text |Cite
|
Sign up to set email alerts
|

Joint Inversion for Sound Speed Field and Moving Source Localization in Shallow Water

Abstract: This paper develops a joint approach for time-evolving sound speed field (SSF) inversion and moving source localization in shallow water environment. The SSF is parameterized in terms of the first three empirical orthogonal function (EOF) coefficients. The approach treats both first three EOF coefficients and source parameters (e.g., source depth, range and speed) as state vectors of evolving with time, and a measurement vector that incorporates acoustic information via a vertical line array (VLA), and then th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…To reduce the degrees of freedom, the SSP is often represented in terms of EOFs [10]. In a previous paper, we verified the inversion of SSP has a good agreement with the measured data [11]. The discrete adjacent SSPs in each time interval are combined to form the SSF in the whole period.…”
Section: Introductionmentioning
confidence: 55%
See 2 more Smart Citations
“…To reduce the degrees of freedom, the SSP is often represented in terms of EOFs [10]. In a previous paper, we verified the inversion of SSP has a good agreement with the measured data [11]. The discrete adjacent SSPs in each time interval are combined to form the SSF in the whole period.…”
Section: Introductionmentioning
confidence: 55%
“…In practice, the number of EOFs representation can be reduced. It is known that the first three EOFs are capable of representing SSP [11], the second block is given by…”
Section: A State Space-model For Trackingmentioning
confidence: 99%
See 1 more Smart Citation
“…In practice, the number of EOF representations can be reduced. In our previous work, it was shown that the first three EOFs are capable of representing SSP [23]. The second block is given by:…”
Section: The State Equation: Moving Source and Environment Parameter Modelingmentioning
confidence: 99%